2019
DOI: 10.1200/jco.19.01367
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter, Prospective, Phase II and Biomarker Study of High-Dose Bevacizumab as Induction Therapy in Patients With Neurofibromatosis Type 2 and Progressive Vestibular Schwannoma

Abstract: PURPOSE Bevacizumab treatment at 7.5 mg/kg every 3 weeks results in improved hearing in approximately 35%-40% of patients with neurofibromatosis type 2 (NF2) and progressive vestibular schwannomas (VSs). However, the optimal dose is unknown. In this multicenter phase II and biomarker study, we evaluated the efficacy and safety of high-dose bevacizumab in pediatric and adult patients with NF2 with progressive VS. PATIENTS AND METHODS Bevacizumab was given for 6 months at 10 mg/kg every 2 weeks, followed by 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 21 publications
3
67
0
Order By: Relevance
“…6,7 To this effect, bevacizumab has been described in numerous adult studies to be an effective therapy to ameliorate both hearing loss and radiological progression of NF2-related vestibular schwannomas, but pediatric data are lacking. [7][8][9][10][11] To address this, we assess a retrospective international cohort of pediatric patients with NF2-associated vestibular schwannomas treated with bevacizumab. Our results suggest that responses may not be as robust as observed in adults, and longer duration of therapy may be necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 To this effect, bevacizumab has been described in numerous adult studies to be an effective therapy to ameliorate both hearing loss and radiological progression of NF2-related vestibular schwannomas, but pediatric data are lacking. [7][8][9][10][11] To address this, we assess a retrospective international cohort of pediatric patients with NF2-associated vestibular schwannomas treated with bevacizumab. Our results suggest that responses may not be as robust as observed in adults, and longer duration of therapy may be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that inhibition of the VEGF pathway, using the monoclonal antibody bevacizumab, could result in hearing improvement, reduction of the tumor volume, or both 6,7 . To this effect, bevacizumab has been described in numerous adult studies to be an effective therapy to ameliorate both hearing loss and radiological progression of NF2‐related vestibular schwannomas, but pediatric data are lacking 7‐11 . To address this, we assess a retrospective international cohort of pediatric patients with NF2‐associated vestibular schwannomas treated with bevacizumab.…”
Section: Introductionmentioning
confidence: 99%
“…Available and well-investigated treatment options are limited to surgery with variable degrees of resection extents [ 5 , 27 ], long-term systemic treatment with bevacizumab [ 9 , 28 , 29 ] and radiation [ 30 ] but the responses are heterogeneous and can be associated with side-effects and complications. Radical total tumor removal carries a high risk of surgically induced deafness as we could show that hearing preservation is dependent on the extent of resection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is recommended in case of symptomatic or growing tumors and GTR can be reached in most cases. Radiotherapy should be used with caution and only when absolutely necessary, especially in hereditary diseases; indeed, in these patients the use of radiation therapy could increase the risk of a malignant tumor in the radiation field ( 107 ) Bevacizumab, an antiangiogenic drug, could also be beneficial in spinal cord lesions due to its promising activity in neurofibromatosis type 2-associated vestibular schwannomas ( 108 ); moreover, lapatinib and nilotinib in combination with radiotherapy demonstrated some benefit in a preclinical model of NF2 associated peripheral schwannoma ( 109 ).…”
Section: Spinal Cord Tumorsmentioning
confidence: 99%